Gender Difference Response of Male and Female Immunodeficiency Rats Treated with Tissue-specific Biomolecules - Fedulova, Liliya V.; Basov, Alexandr A.; Vasilevskaya, Ekaterina R.; Dzhimak, Stepan S. (Current Pharmaceutical Biotechnology, 2019)
Background: The modern immunology is targeted to the detailed study of various immunopathological conditions at the molecular and cellular level, development of new methods for the prevention, diagnostics and treatment of contagious and non-contagious diseases of humans and animals. Methods: In the present work we took the rats with model of cyclophosphamide-induced immunodeficiency and studied the features of gender impact of the complex extract of immunocompetent organs (thymus, spleen and mesenteric lymph nodes) Sus scrofa and its separate fraction with molecular weight less than 30 kDa administered to male and female rats. Results: The impact of gender differences and tissue-specific biomolecules (30 kDa fraction) on hematological parameters (leukocytes, erythrocytes, platelets), functional activity of immune system (IL-2, IL-4, IL-6, complement system, IgG, IgM), biochemical parameters of hepatocytes functioning (activity of ALP and LDG), carbohydrate metabolism (glucose) and lipid metabolism (triglycerides). Conclusion: Decrease of ALP activity is caused by inhibition of bile formation in a liver after introduction of cytostatic agent, and in contrast to complex extract, the administration of fraction 30 kDa allows improving bile production in male rats.
Keywords: immunocompetent organ